2018
DOI: 10.1039/c8em00016f
|View full text |Cite
|
Sign up to set email alerts
|

Mercury behaviour and C, N, and P biogeochemical cycles during ecological restoration processes of old mining sites in French Guiana

Abstract: Several decades of gold mining extraction activities in the Amazonian rainforest have caused deforestation and pollution. While ecological rehabilitation is essential for restoring biodiversity and decreasing erosion on deforested lands, few studies note the behaviour or toxicity of trace elements during the rehabilitation process. Our original study focused on the potential use of microbial activity and Hg speciation and compared them with As, Cu, Zn and Cr speciation in assessing the chemical and biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 108 publications
3
16
1
Order By: Relevance
“…Firstly, there were significant differences in soil microbial biomass, which were related with the density and quality of the vegetation cover on the restored sites. These results, already highlighted by various works on rehabilitated sites, confirm the contribution of successful ecological restoration in the recovery of soil microbial biomass [ 39 , 42 , 43 , 44 ], especially on the rehabilitated sites of Yaoni.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Firstly, there were significant differences in soil microbial biomass, which were related with the density and quality of the vegetation cover on the restored sites. These results, already highlighted by various works on rehabilitated sites, confirm the contribution of successful ecological restoration in the recovery of soil microbial biomass [ 39 , 42 , 43 , 44 ], especially on the rehabilitated sites of Yaoni.…”
Section: Discussionsupporting
confidence: 78%
“…Several authors have highlighted similar results. Anderson [ 37 ] showed that the affinity for and retention of mercury in organic matter in acidic soils could exceed the affinity for metal oxides, as confirmed by recent studies on mercury speciation at former Guyanese mining sites [ 34 , 42 ]. Roulet and Lucotte’s [ 16 ] work highlighted that mercury retention in Guyanese soils was not always correlated with the presence of metal oxides.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This change provides a good template for us to study the process of natural coordinated plant-soil recovery under temporal changes (Zhao et al, 2013). Especially, the ecological stoichiometry that is an important indicator reflecting the carbon (C), nitrogen (N) and phosphorous (P) cycles inside the soil (Zechmeister-Boltenstern et al, 2015) integrates the variability of ecosystem function and is widely used in the study of limitative nutrient element determination (Zhou et al, 2018), biogeochemical cycles and population dynamics (Martiny et al, 2016;Busch et al, 2018;Couic et al, 2018). During the process of secondary succession of abandoned farmlands, the relationship between the changes in ecological stoichiometric ratio and the aboveground plant community succession is unknown.…”
Section: Introductionmentioning
confidence: 99%